Screening for coronary heart disease risk factors in retail pharmacies in Sheffield, 1992. Issue 2 (April 1994) - Allison, C; Page, H; George, S
Abstract : OBJECTIVE–To investigate the current and likely future provision of screening services for risk factors for coronary heart disease in retail pharmacies in Sheffield. DESIGN–This was a questionnaire survey asking about screening tests currently offered, price charged per test, likely future provision of screening tests, the action respondents would take upon finding an abnormal test result, whether the pharmacy was owner-run, franchised, or part of a commercial chain, and inviting open comments from respondents. SETTING–All retail pharmacy premises on the Sheffield Family Health Services Authority list. RESULTS–Seventy seven responses were obtained to 102 questionnaires distributed. Only nine of these currently offered any screening test other than pregnancy testing, although 37 indicated that they might offer tests in the future. Thirty nine were not offering screening and had no plans to do so. Pharmacies offering or likely to offer screening tests were mainly owner-run. All pharmacists who replied to the question asking about their action upon finding abnormal result (33) reported that they would advise the patient to see a doctor. The most frequent comments made by pharmacists were about the commercial viability of screening in pharmacies and the lack of space available to ensure patient privacy and confidentiality during screening. CONCLUSIONS–Screening in retail pharmacies would probably be a commercial failure unless doctors were able to contract for screening services from pharmacies. Evidence from this study and others, however, leads us to question the desirability of this option.